1995
DOI: 10.1086/175678
|View full text |Cite
|
Sign up to set email alerts
|

Probable gravitational microlensing toward the galactic bulge

Abstract: The MACHO project carries out regular photometric monitoring of millions of stars in the Magellanic Clouds and Galactic Bulge, to search for very rare gravitational microlensing events due to compact objects in the galactic halo and disk. A preliminary analysis of one eld in the Galactic Bulge, containing 430; 000 stars observed for 190 days, reveals four stars which show clear evidence for brightenings which are time-symmetric, achromatic in our two passbands, and have shapes consistent with gravitational mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 7 publications
9
122
0
1
Order By: Relevance
“…The RR Lyrae trace metal-poor stars, which are a minor component of the bulge population. The clump giants, however, should trace the bulk of the metal-rich population, foUowing underlying mass of the bulge more closely Given the different spatial distribution, we concluded that the RR Lyrae and the clump giants trace two dif+erent populations (Alcock et al 1998). The RR Lyrae would represent the inner extension of the Galactic halo in these fields (Minniti 1996).…”
Section: Eso Notre Dame Oxford and Memastermentioning
confidence: 75%
See 1 more Smart Citation
“…The RR Lyrae trace metal-poor stars, which are a minor component of the bulge population. The clump giants, however, should trace the bulk of the metal-rich population, foUowing underlying mass of the bulge more closely Given the different spatial distribution, we concluded that the RR Lyrae and the clump giants trace two dif+erent populations (Alcock et al 1998). The RR Lyrae would represent the inner extension of the Galactic halo in these fields (Minniti 1996).…”
Section: Eso Notre Dame Oxford and Memastermentioning
confidence: 75%
“…The distribution along the line of sight of the bulge RR Lyrae population was examined on the basis of the mean magnitudes, and it was shown that the bulk of the RR Lyrae population is not barred (Alcock et al 1998). There is a hint of a bar only in the RR Lyrae of the inner fields closer to the Galactic center (t <4°, b > -40).…”
Section: Eso Notre Dame Oxford and Memastermentioning
confidence: 99%
“…The optical depth to microlensing towards the galactic bulge was found to be 3 10 6 (Udalski et al 1994b, Alcock et al 1995c, while the original theoretical estimates were below 10 6 , Griest et al 1991. Theoretical estimates were increased by Kiraga & Paczy nski (1994) to somewhat above 10 6 when the importance of self-lensing by the bulge was recognized, and increased even more when the importance of the galactic bar was noticed .…”
Section: Past and Presentmentioning
confidence: 93%
“…The first such event observed was reported by Alcock et al (1995). It is the longest of their 45 microlensing events detected towards the Galactic bulge in their first year of observation ).…”
Section: Parallax Effectsmentioning
confidence: 93%
“…Since the event is achromatic, there is little doubt that this is a bona fide microlensing event, despite the deviation from the symmetric PSPL-shape. Alcock et al (1995) discuss the nature of the deviation from linear motion and emphasize that it is impossible to distinguish between the possibilities that motions of lens, source or observer lead to this modification. However, with the knowledge of the orbital parameters of the Earth, they tried to fit the lightcurve and argued that their reasonable fit with these assumptions is a strong argument in favour of Earth's motion really causing the deviations.…”
Section: Parallax Effectsmentioning
confidence: 99%